Mecanismos envolvidos no atenuamento da inflamação pulmonar alérgica em ratos com baixo peso ao nascer - Ramos, Ana Paula Almeida [UNIFESP] (2018)
Food restriction during the gestational period leads to changes in the pattern of fetal growth and development. In previous studies, our group demonstrated that intrauterine malnutrition caused elevated levels of basal corticosterone and reduced allergic lung inflammatory response in Wistar rats. Based on these findings, the present study aimed to evaluate mechanisms involved in the attenuation of the allergic pulmonary inflammatory response, such as the role of corticosterone and epigenetic alterations. Male Wistar rats, with low birth weight (LBW), from malnourished females during the whole gestational period, with 9 weeks of age were sensitized and challenged with ovalbumin. Allergic pulmonary response was studied in these animals at 12 weeks of age. The characterization of the inflammatory response was analyzed by analysis of the cellular infiltrate in the bronchoalveolar lavage and histological section of the peribronchial region, where we verified a lower cellular infiltrate in the LBW lungs. The quantification of IgE, cytokines, ACTH and CORT was performed by multiplex assay and quantification of CBG, PGE2 and DNMT1 by Kit EIA. Gene expression of 11βHSD1, 11β-HSD2, COX-1, COX-2, GR and RUNX3 was evaluated by RT-PCR Real Time, while the protein expression of COX-1, COX-2 and GR was evaluated by Western blotting. Global DNA methylation quantified by Methylamp global DNA methylation. LBW rats sensitized and challenged with ovalbumin (OVA/OVA) demonstrated lower serum IgE levels than normal birth weight (NBW) rats OVA/OVA. It was observed an imbalance in cytokines production, in LBW rats: elevated basal levels of IL-4 and IL-10 with consequent failure to increase these cytokines after stimulation with OVA; failure to raise levels of IL-5 and IL-6 and lower IL-13 levels after OVA challenge, in addition to higher levels of IL-1β, TNF-α and IFN-γ. PGE2 levels were lower in LBW OVA/OVA rats than NBW OVA/OVA rats. LBW OVA/OVA rats failed to increase the gene and protein expression of the COX-1 and COX-2 enzymes. LBW rats presented high basal levels of CORT and failed to increase these levels after challenge with OVA, different from that observed in NBW OVA/OVA rats. On the other hand, the challenge with OVA did not modify ACTH levels in LBW rats, whereas in NBW OVA/OVA rats it caused reduction. After stimulation with OVA, only NBW rats demonstrated a reduction in GR expression; the expression of 11β-HSD2 did not differ when compared LBW vs. NBW groups, and the LBW OVA/OVA vs. NBW OVA/OVA groups, but LBW group failed to increase 11β-HSD2 expression after OVA stimulation.There was no difference in CBG levels among different groups. Global methylation levels as well as DNMT1 enzyme levels were significantly higher in LBW OVA/PBS rats compared to NBW OVA/PBS; only LBW OVA/OVA rats decreased the concentration of DNMT1. The RUNX3 gene expression did not differ when compared LBW vs. NBW groups and the LBW OVA/OVA vs. NBW OVA/OVA groups. Considering these results, we propose that the failure in corticosterone regulation and the imbalance in the production of inflammatory mediators, together with DNA hypermethylation in lung tissue could be involved in the attenuation of the allergic inflammatory response presented by LBW rats.